A method for detecting leakage performance of PE membrane materials

By using soybean oil standard solution to simulate urine and feces in the PE membrane detection method, combined with the observation and calculation of the color phenomenon, the problem that existing detection methods cannot quickly and effectively detect the leakage performance of PE membrane is solved, and a rapid and accurate leakage performance evaluation of PE membrane products is achieved.

CN114324119BActive Publication Date: 2025-04-25GUIZHOU KABU BABY PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210042245.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-14
Publication Date
2025-04-25
Estimated Expiration
2042-01-14

AI Technical Summary

Technical Problem

The existing PE film leakage performance detection methods cannot quickly and effectively detect leakage quality defects in PE film materials, and cannot simulate and reflect the user's real experience more intuitively and correctly.

Method used

A detection method including preparing a test environment, preparing a simulation test fluid, performing tests, ending tests and determining results is adopted. The specific steps include placing absorbent paper on the plastic film, preparing a simulation test solution containing a standard soybean oil solution, dropping the test solution on the absorbent paper, placing the PE film to be tested and applying weights, observing the patina phenomenon and calculating the patina area and quantity to judge the leakage performance.

Benefits of technology

The intuitive, easy-to-operate, and quantitative leakage performance level classification of PE film products is achieved, and the anti-leakage performance of PE film can be quickly and accurately identified, thereby improving the production process and improving the production quality of absorbents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114324119B_ABST
    Figure CN114324119B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of absorbent product performance detection, and discloses a method for detecting the leakage performance of a PE film material, comprising the steps of preparing a test environment, preparing a simulated test liquid, conducting a test, ending the test, determining a result, and the like. The present invention can reasonably and effectively classify the leakage performance levels of PE film products, especially cast film and blown film, in an intuitive, easy-to-operate, and quantitative manner, and provides corresponding qualified determination criteria. PE film product developers can intuitively and accurately observe the test results that are basically consistent with the actual user experience, quickly find the defective positions of the PE film products, find the direction of improving the subsequent production process flow, and find the PE film products that are most suitable for a specific application environment, thereby improving the production quality of absorbent products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of a rapid testing method for the performance of absorbent products, and specifically relates to a leakage testing method for a PE film material. Background Art

[0002] PE film materials are widely used in the field of sanitary products, such as sanitary napkins, diapers, and nursing pads. Almost all production processes in the sanitary products industry use PE film between the core and the base film to give full play to the water-repellent and leak-proof functions of the PE film. In actual applications, due to the quality defects of PE film materials, leakage problems often occur in the final product, and the products entering the market will cause a bad user experience for users.

[0003] In the prior art, most of the PE membrane leakage performance detection methods usually use physiological saline as the test liquid to simply simulate the composition of urine for leakage detection, and the tester directly observes the leakage of physiological saline with the naked eye. However, in actual use, users, especially infants and young children, not only produce urine but also feces, and feces will have a substantial impact on the leakage performance of PE membranes. If the PE membrane product itself has obvious defects during molding, this impact will be amplified, resulting in a decrease in the anti-leakage performance of the PE membrane product, causing it to not function normally, affecting the user's daily use experience. In other words, the existing detection methods cannot quickly and effectively detect the leakage quality defects of PE membrane materials, and are also not good at intuitively and correctly simulating and reflecting the user's real experience. Summary of the invention

[0004] In view of the technical defects existing in the background technology, the present invention proposes a method for detecting the leakage performance of PE membrane materials, which solves the above technical problems and meets the actual needs. The specific technical solution is as follows:

[0005] A method for detecting leakage performance of PE film materials, comprising:

[0006] A) Prepare the test environment, prepare a leakproof cushion, place at least one layer of plastic film on the cushion, and then place at least five layers of absorbent paper on the plastic film;

[0007] B) Prepare a simulated test solution by adding 5 parts of food-grade brilliant blue and 100 parts of soybean oil standard solution to 1000 parts of normal saline and stirring evenly;

[0008] C) To conduct the test, take 10 portions of the simulated test liquid, drip it onto the center of the topmost absorbent paper and let it stand for 30 seconds. Place the PE film to be tested on the absorbent paper with the use side facing up, place a piece of absorbent paper on the PE film, and then place a weight of 5 kg;

[0009] D) After the test, remove the weight once at the unit time T and every time point n×T, and observe whether there is any color bleeding on the absorbent paper on the PE film each time;

[0010] E) Determine the results, calculate the infiltration area and the number of infiltration surfaces, and use this as a basis to determine the leakage performance.

[0011] As a further technical solution of the present invention, the soybean oil standard solution includes soybean oil, emulsifier, 1,2-propylene glycol, and secondary pure water with a conductivity of ≤3.0μs / cm. The soybean oil standard solution is used to simulate human urine and feces and produce fatty acids that affect the permeability of the PE membrane.

[0012] As a further technical solution of the present invention, the soybean oil, emulsifier, 1,2-propylene glycol and secondary pure water are contained in a ratio of 1:2:2:100.

[0013] As a further technical solution of the present invention, the preparation method of the soybean oil standard solution is to pour the weighed emulsifier, soybean oil, and 1,2-propylene glycol into a beaker in sequence, stir evenly until the mixed liquid has no obvious particles, pour in secondary pure water and stir evenly again to obtain the soybean oil standard solution.

[0014] As a further technical solution of the present invention, in the step E, the color bleed area and color bleed spots determined by the results are based on the values ​​of the film paper stains, scratches and debris measurement charts, which include the following three grades: Grade A leakage performance means that color bleed spots with a color bleed area ≥3.0 square millimeters are not allowed to appear; Grade B leakage performance means that the number of color bleed spots with a color bleed area of ​​1-3 square millimeters does not exceed 5; Grade C leakage performance means that the number of color bleed spots with a color bleed area ≤1 square millimeter does not exceed 10.

[0015] As a further technical solution of the present invention, the value of T is 5 min, the value of n is 1, 2, 3, 4, 5, 6, and the value of n×T is a leakage time simulated under different usage time.

[0016] As a further technical solution of the present invention, the PE film includes two types: cast film and blown film, and a consistent judgment standard is adopted.

[0017] Since the PE film is a protective structure for absorbent products to prevent leakage, it is set on the outside of the diaper and does not directly participate in the absorption process of the diaper. Compared with the water absorption performance of the core, it is not so easy to attract the attention of general users. However, its anti-leakage ability is related to the extent of the absorbent product's impact on the outside world and the key to the user experience.

[0018] Therefore, the beneficial effect of the present invention is that the present invention can reasonably and effectively classify the leakage performance levels of PE film products, especially cast film and blown film, in an intuitive, easy-to-operate and quantitative manner, and provides corresponding qualified judgment basis. PE film product developers can intuitively and accurately observe the test results that are basically consistent with the actual user experience, and quickly find the defective locations of the PE film products, so that PE film product developers can quickly and accurately identify the anti-leakage performance of the PE film through the corresponding test data, thereby finding the direction to improve the subsequent production process flow, and finding the PE film product that is most suitable for a specific application environment, thereby improving the production quality of absorbent products. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the appearance of the absorbent paper pile before the test.

[0020] Figure 2 This is a schematic diagram of the stained appearance of a pile of absorbent paper after a simulated test liquid containing bright blue was added during the test.

[0021] Figure 3 This is a schematic diagram of the state of adding the PE film to be tested during the test.

[0022] Figure 4 This is a schematic diagram of the state after the counterweight is applied during the test.

[0023] Figure 5 The figure shows the test result after adding 5 mL of simulated test solution containing soybean oil.

[0024] Figure 6 The figure shows the test result after adding 10 mL of simulated test liquid containing soybean oil.

[0025] Figure 7 The figure shows the test result after adding 15 mL of simulated test liquid containing soybean oil.

[0026] Figure 8 The figure shows the test result after adding 5 mL of simulated test solution containing rapeseed oil.

[0027] Fig. 9 The figure shows the test result after adding 10 mL of simulated test solution containing rapeseed oil.

[0028] Fig.10 The figure shows the test result of adding 10 mL of physiological saline solution to simulate the test solution.

[0029] Fig.11 The test results are as follows: 10 mL of simulated test solution containing edible oil was added. DETAILED DESCRIPTION

[0030] The implementation modes of the present invention are described below in conjunction with the accompanying drawings and relevant embodiments. The implementation modes of the present invention are not limited to the following embodiments, and the present invention relates to relevant necessary components in the technical field, which should be regarded as the known technology in the technical field and can be known and mastered by the technical personnel in the technical field.

[0031] Combination Figures 1 to 4 As shown, a method for detecting leakage performance of PE film material comprises:

[0032] A) Prepare the test environment, prepare a leakproof cushion, place at least one layer of plastic film on the cushion, and then place at least five layers of absorbent paper on the plastic film;

[0033] B) Prepare a simulated test solution by adding 5 parts of food-grade brilliant blue and 100 parts of soybean oil standard solution to 1000 parts of normal saline and stirring evenly;

[0034] C) To conduct the test, take 10 portions of the simulated test liquid, drip it onto the center of the topmost absorbent paper and let it stand for 30 seconds. Place the PE film to be tested on the absorbent paper with the use side facing up, place a piece of absorbent paper on the PE film, and then place a weight of 5 kg;

[0035] D) After the test, remove the weight once at the unit time T and every time point n×T, and observe whether there is any color bleeding on the absorbent paper on the PE film each time;

[0036] E) Determine the results, calculate the infiltration area and the number of infiltration surfaces, and use this as a basis to determine the leakage performance.

[0037] When preparing the test environment, the size of the plastic film used as the cushion layer of the PE film sample to be tested must be larger than the absorbent paper. In this test method, the role of the absorbent paper is to simulate the leakage of cores of different thicknesses when absorbing the simulated test liquid for different lengths of time. For the same purpose, the size of the PE film sample to be tested should also be smaller than the size of the absorbent paper, so as to ensure that the PE film samples to be tested are all in the same test environment during the test; in the present invention, in order to better observe the color penetration effect, if the filter paper used for general air permeability test or water absorption test is replaced by the absorbent paper in the present invention, the color penetration effect cannot reach the obvious effect visible to the naked eye disclosed in the present invention, and at the same time, it is impossible to correctly simulate the actual leakage after the core absorbs water in actual use, so the absorbent paper cannot be replaced by the filter paper.

[0038] The simulated test liquid uses physiological saline to imitate human urine, which is the most common and reproducible simulated liquid for testing the performance of absorbent products in this field. The difference in the present invention is that it uses physiological saline to imitate urine supplemented with soybean oil to simulate the amount of fat content remaining in the loose stool after infants and young children suck breast milk with different fat contents and emulsify and absorb it. 5ml, 10mL, and 15ml correspond to the light, medium, and severe test leakage conditions of fat content, respectively. At the same time, since it is necessary to measure the area of ​​the infiltration color by naked eyes, transparent mm grids, or debris measurement charts, etc., in order to calculate the reference for judging the leakage performance, 5 parts of food-grade brilliant blue are added to every 1000 parts of the test liquid. On the one hand, it will not change the permeability of the test liquid itself, and on the other hand, it will make the color of the infiltration color more intuitive and easy to measure.

[0039] In the test method of the present invention, in addition to being able to intuitively see the leakage of different PE films under quantifiable experimental conditions, and to measure the area of ​​infiltration by naked eyes, transparent mm grids or debris measurement charts, etc., so as to directly obtain the corresponding performance grade data of the PE film test sample, at the same time, because it can simulate the influence of feces on the performance of PE film, through the addition of its bright blue color, without affecting the simulation effect of the test liquid, the test developers can quickly find the defective areas on the surface of the PE film product that are invisible to the naked eye through the infiltration situation, thereby allowing the developers to more intuitively observe the performance of the product from the user's perspective and find existing problems and improvement directions.

[0040] At the same time, in the preferred embodiment, the three volumes of 5mL, 10mL and 15mL can also simulate the urine leakage of different age stages. The volume of the test liquid added by the present invention needs to be set in a gradient. It is more intuitive to judge whether it meets the test judgment standard through the leakage area and leakage point.

[0041] In the specific test, considering that the PE film is used as the bottom film, except for the occasion when the user sits or lies down, the absorbent is compressed and the PE film is also compressed to passively contact the exudate of the core. Most of the time, the user is in an active state. At the same time, in order to be able to operate the test tool more quickly to add samples, test and take samples. Unlike the conventional selection of the technology in this field or the common sense of the technicians, in the test method disclosed in the present invention, the product to be tested is placed under the liquid source and pressure is applied from top to bottom to test the absorption capacity. Waiting for 30 seconds is to allow the absorbent paper layer to fully restore the state of the absorbent core after absorbing water. The PE film to be tested is placed on the absorbent paper layer with the test liquid dripped on it, and then the absorbent paper for collecting the test results is placed on the top of the PE film to be tested, and a 5kg counterweight is applied. In this way, it is convenient for the tester to take samples, and it can also restore the situation where the user's clothes exert pressure on the absorbent when he is in an active state. The pressure size in this occasion usually does not exceed the pressure caused by the 5kg counterweight.

[0042] In order to collect the color penetration data of the PE film product to be tested as accurately as possible within a reasonable time, and at the same time quantify the test results and reduce the errors caused by accidental factors, in the present application, the data of the same PE film product to be tested is recorded no less than once, and the color penetration result is recorded once per unit time T. From the perspective of quantifying the test time and the convenience of recording the test results, the preferred value of the unit time T is 5 minutes, and the maximum value of n does not exceed 6, that is, 30 minutes is the longest test time for a single PE test sample.

[0043] For the purpose of quantifying leakage performance, the test method disclosed in the present invention is to measure the area of ​​the infiltration points based on stain, scratch and debris measurement charts and transparent mm grids. This can facilitate testers to accurately quantify the ever-changing infiltration patterns, avoid the problem of calculating the infiltration area being too difficult, shorten the time for result recording and analysis, and is conducive to large-scale testing of product performance. It also meets the fundamental purpose of accelerating technological research and development.

[0044] In the present invention, soybean oil standard solvent is used as an additive for physiological saline. Its fundamental purpose is to add an emulsifier to soybean oil to simulate the fat residue after human body absorption and emulsification. Because the critical point of the emulsifier is 70°C, 1,2-propylene glycol is added to better dissolve the configured solution. And also for the stability of the color pattern display, especially for the test of PE film, because the PE film is triggered from the perspective of leakproof, the water absorption performance is far inferior to the polymer material used for the absorbent core and the surface layer. Therefore, in order to facilitate color development and the diffusion of brilliant blue, it is also necessary to configure physiological saline with soybean oil standard solvent added for testing. In addition, as a reference, the present invention introduces rapeseed oil standard solvent as a control group for testing to prove the accuracy and effectiveness of physiological saline added with soybean oil standard solvent, which will be explained below.

[0045] In the preferred embodiment of the present invention, 1000 mL of normal saline was added with 0.5 g of food-grade brilliant blue and 100 mL of soybean oil standard solution. At the same time, a rapeseed oil standard solution was added as a control group to compare the difference between the two. The test results below are directly obtained after experiments based on the test parameters in this embodiment.

[0046] Reference Figure 3 , Figure 4 As shown, in order to better quantify the test results and increase the persuasiveness, under the preferred embodiment of the present invention, the PE film sample to be tested is selected to have a diameter of 200 mm, which is suitable for the shape of absorbent paper. At the same time, in order to prepare the test liquid and conduct the test, it is also necessary to prepare an electronic balance, a stopwatch, a kettle, a 250ml beaker, a glass rod, a rubber-tipped dropper, a 100ml, 10ml, 5ml measuring cylinder, a 500ml plastic measuring cup, a thermometer, a 5kg weight, stains, scratches, transparent mm grids, debris measurement charts and other necessary instruments or objective reference materials.

[0047] As a further technical solution of the present invention, the soybean oil standard solution includes soybean oil, emulsifier, 1,2-propylene glycol, and secondary pure water with a conductivity of ≤3.0μs / cm. The soybean oil standard solution is used to simulate human urine and feces and produce fatty acids that affect the permeability of the PE membrane. In order to better mix the secondary pure water with a conductivity of ≤3.0μs / cm with the emulsifier, soybean oil and 1,2-propylene glycol, the temperature used is preferably 70°C because the critical emulsification temperature of the emulsifier is 70°C. After testing, it is not the best option to be lower or higher than the critical emulsification temperature, so it should meet the determined value.

[0048] The soybean standard solution used in the present invention is intended to simulate the urine and feces components of users, especially infants and young children. The reason is that there are generally only inorganic salts in urine, and inorganic salts have no effect on the permeability of PE membranes, but feces contain fatty acids, and fatty acids have an effect on the performance of PE membranes, and this effect is directly reflected in the decline of the anti-permeability performance of PE membranes. The specific reasons are: first, the main raw material of PE membrane is low-density polyethylene, and chain transfer reaction occurs during synthesis. There are gaps between polymer chains, and the gaps may be larger than oil molecules during production; second, PE membrane and fatty acids are both non-polar molecules, and they will dissolve each other, that is, the principle of similar dissolving, and the contact between the two will cause the micropore diameter of the PE membrane to change, thereby causing changes in air permeability and waterproof performance. Based on the above reasons, after the PE membrane contacts the feces of infants and young children containing fatty acids, it is very easy to cause leakage, which will cause inconvenience in use. However, the existing physiological saline test solution cannot reflect the above phenomenon more truly and accurately. Therefore, in order to better grasp the anti-permeability performance of PE membranes, general physiological saline biomimetic liquid is not enough to meet the test requirements.

[0049] As a further technical solution of the present invention, the soybean oil, emulsifier, 1,2-propylene glycol and water are contained in a ratio of 1:2:2:100. Specifically, when quantified in the test method under the preferred embodiment of the present invention, they should be 1 mL, 2 mL, 2 mL and 100 mL respectively.

[0050] As a further technical solution of the present invention, the preparation method of the soybean oil standard solution is to pour the weighed emulsifier, soybean oil, and 1,2-propylene glycol into a beaker in sequence, stir evenly until the mixed liquid has no obvious particles, pour in secondary pure water and stir evenly again to obtain the soybean oil standard solution.

[0051] If the PE film has uniform thickness and texture, and the pore opening process is good, then if it is modified by fatty acids, the modification should also be uniform. However, this is only an ideal state. The actual situation is that it is difficult to ensure that the PE film can perfectly complete the film forming and pore opening operations during processing. In this way, the film thickness in some areas will inevitably not reach the average level, and once this part of the film is modified, it is very easy to cause leakage. In order to allow the colorant to be clearly displayed on the PE film to be tested, another important function of the soybean oil standard solution in the present invention is to directly affect the PE film, causing it to denature, and amplify the size of the micropores at the defective position, inducing the color penetration of the PE film, so that the tester can distinguish the defects on the surface of the PE film and other parameters related to the measurement of permeability through the color penetration. Otherwise, the actual processing situation of the PE film cannot be so intuitively and simply reflected, and the modification of the PE film cannot be caused by physiological saline, which is not conducive to quickly and accurately simulating the user's actual usage experience.

[0052] In order to further illustrate, the present invention will use different proportions of different types of oil to verify the optimal value of the addition amount - data verification, so as to ensure that the color-infiltrating effect can detect the permeability of the PE film, in other words, to detect whether the pore size distribution and thickness distribution on the surface of the PE film are uniform, and the specific test results are given below. It should be pointed out that the existing air permeability test is generally tested with water or saline. After applying pressure to the PE film to which saline or pigmented saline is added, whether water droplets seep out is judged to determine the air permeability of the PE film, but the anti-leakage property is related to fecal excrement containing more fatty acids. A very important reason is that the amount of urine of infants and young children is larger than the amount of feces, and their main diet is breast milk or blended milk. In addition to water, the main components of the total excrement contain more fatty acid components that affect the permeability of the PE film. Once the physical properties of the PE film are changed due to the fatty acids in the feces, it will affect the user experience of infants and young children. Therefore, in order to accurately obtain the actual experience record of the user, it is necessary to use oil as a test liquid additive.

[0053] As a further technical solution of the present invention, the value of T is 5 minutes, the value of n is 1, 2, 3, 4, 5, 6, and the n×T value is a value for simulating leakage time under different usage durations. By intervalizing the leakage time, the test data composition can be quantified more accurately, which is convenient for developers to judge the actual performance change curve of PE film products, thereby grasping the more likely reasons that may affect the leakage performance.

[0054] As a further technical solution of the present invention, the PE film includes two types: cast film and blown film, and a consistent judgment standard is adopted. Since the commonly used materials for PE film are generally cast film and blown film, only the above two materials are considered in the test method disclosed in the present invention, and other materials with similar performance can also refer to the test process of the above two materials and adopt a consistent test result comparison method.

[0055] As a further technical solution of the present invention, in the step E, the color bleed area and color bleed spots determined by the results are based on the values ​​of the film paper stains, scratches, and debris measurement charts, which include the following three grades: Class A leakage performance means that color bleed spots with a color bleed area ≥3.0 square millimeters are not allowed to appear; Class B leakage performance means that the number of color bleed spots with a color bleed area of ​​1-3 square millimeters does not exceed 5; Class C leakage performance means that the number of color bleed spots with a color bleed area ≤1 square millimeter does not exceed 10. This is because, when the color bleed phenomenon is more obvious, the diaper product is actually in a situation where it needs to be replaced. Therefore, the above-mentioned determination marking is more in line with the test results under the actual experience environment when the diapers are actually used. At the same time, since absorbent paper is used as the test substrate to simulate the absorbent core, the color bleed will be more obvious and easy to observe.

[0056] Based on the test environment and test sample specifications in the preferred embodiment mentioned above, the present invention discloses the test results of a standard solution based on soybean oil and a standard solution based on rapeseed oil on blown film and cast film of the same specifications, and the sampling time is 5 minutes, 10 minutes, 15 minutes, 20 minutes and 30 minutes. Figures 5 to 11 In the figure, the results in the left column are all blown film, while the results in the right column are all cast film. The specific test results are as follows:

[0057] Soybean oil standard solution, reference Figure 5 As shown, 5 mL of test liquid was added, and the blown film pressed for 5 minutes had 5 color points and a color area of ​​2.4 square millimeters, while the cast film had no color and no color area; the blown film pressed for 10 minutes had 10 color points and a color area of ​​9.65 square millimeters, while the cast film had no color and no color area; the blown film pressed for 15 minutes had more than 50 color points and a color area of ​​more than 200 square millimeters, while the cast film had 2 color points and a color area of ​​1.2 square millimeters; the blown film pressed for 20 minutes had more than 50 color points and a color area of ​​more than 300 square millimeters, while the cast film had 3 color points and a color area of ​​0.6 square millimeters; the blown film pressed for 30 minutes had more than 50 color points and a color area of ​​more than 300 square millimeters, while the cast film had more than 30 color points and a color area of ​​more than 30 square millimeters.

[0058] Reference Figure 6 As shown, after adding 10 mL of test liquid, the blown film pressed for 5 minutes had 3 color points and a color area of ​​4.4 square millimeters, while the cast film had no color and no color area; the blown film pressed for 10 minutes had 5 color points and a color area of ​​1.9 square millimeters, while the cast film had 2 color points and a color area of ​​0.9 square millimeters; the blown film pressed for 15 minutes had 5 color points and a color area of ​​5.3 square millimeters, while the cast film had 2 color points and a color area of ​​0.78 square millimeters; the blown film pressed for 20 minutes had 6 color points and a color area of ​​8.8 square millimeters, while the cast film had 2 color points and a color area of ​​1.2 square millimeters; the blown film pressed for 30 minutes had 6 color points and a color area of ​​13 square millimeters, while the cast film had 5 color points and a color area of ​​2.6 square millimeters.

[0059] Reference Figure 7As shown, 15 mL of test liquid was added, and the blown film pressed for 5 minutes had 4 color points and a color area of ​​77 square millimeters, while the cast film had no color and no color area; the blown film pressed for 10 minutes had 21 color points and a color area of ​​52.25 square millimeters, while the cast film had 4 color points and a color area of ​​1.75 square millimeters; the blown film pressed for 15 minutes had 25 color points and a color area of ​​65.15 square millimeters, while the cast film had 6 color points and a color area of ​​9.6 square millimeters; the blown film pressed for 20 minutes had more than 50 color points and a color area of ​​more than 200 square millimeters, while the cast film had more than 21 color points and a color area of ​​14.7 square millimeters; the blown film pressed for 30 minutes had more than 50 color points and a color area of ​​more than 300 square millimeters, while the cast film had more than 30 color points and a color area of ​​24.6 square millimeters.

[0060] Reference Figure 8 As shown, since the cast film has been infiltrated when the addition amount is 10mL, the test process for 15mL is omitted. The test results under the rapeseed oil standard solution are as follows: when 5mL of the test solution is added, the blown film has 4 infiltration points and the infiltration area is 0.2 square millimeters after pressing for 5 minutes, while the cast film has no infiltration and no infiltration area; when the blown film is pressed for 10 minutes, the infiltration points are 6 and the infiltration area is 13.5 square millimeters, while the cast film has no infiltration and no infiltration area; when the pressure is pressed for 15 The blown film pressed for 20 minutes has 9 color points and the color area is 121 square millimeters, while the cast film has 2 color points and the color area is 1.0 square millimeter; the blown film pressed for 20 minutes has 11 color points and the color area is 33.3 square millimeters, while the cast film has 5 color points and the color area is 2.4 square millimeters; the blown film pressed for 30 minutes has 32 color points and the color area is greater than 200 square millimeters, while the cast film has 7 color points and the color area is 6.8 square millimeters.

[0061] Reference Fig. 9 As shown, after adding 10 mL of test liquid, both the blown film and the cast film pressed for 5 minutes had no color infiltration and no color infiltration area; the blown film pressed for 10 minutes had 3 color infiltration points and a color infiltration area of ​​12 square millimeters, while the cast film had no color infiltration and a color infiltration area of ​​0; the blown film pressed for 15 minutes had 12 color infiltration points and a color infiltration area of ​​36 square millimeters, while the cast film had 6 color infiltration points and a color infiltration area of ​​11.7 square millimeters; the blown film pressed for 20 minutes had 24 color infiltration points and a color infiltration area of ​​43.2 square millimeters, while the cast film had 12 color infiltration points and a color infiltration area of ​​19.8 square millimeters; the blown film pressed for 30 minutes had 17 color infiltration points and a color infiltration area of ​​286.9 square millimeters, while the cast film had 8 color infiltration points and a color infiltration area of ​​16.9 square millimeters.

[0062] In order to specifically illustrate the effect of adding oil to simulate urine and feces on the permeability of PE membrane, please refer to Fig.10As shown, the test solution added was 0.5 g of food-grade brilliant blue added to 1000 mL of normal saline, the same 5 kg weight was used as the counterweight, 10 mL of the test solution was added, and other test conditions were consistent with the previous embodiment. No color was shown after pressing for 5 minutes and 10 minutes, indicating that inorganic salt urine has little effect on the anti-permeability performance of the PE film.

[0063] And refer to Fig.11 As shown, 0.5g of food-grade brilliant blue and 15mL of edible oil, specifically peanut oil, were added to 1000mL of normal saline, and the same 5kg weight was used as a counterweight, 10mL of test liquid was added, and other test conditions were consistent with the above-mentioned embodiments. When pressed for 5 minutes, there was no obvious color penetration phenomenon in both the cast film and the blown film, while when pressed for 10 minutes, both the cast film and the blown film produced color penetration phenomenon, indicating that fatty acid is an important factor affecting the change of the anti-permeability performance of the PE film, and also proves that the test method of the present invention can be extended to other oil additives that can produce fatty acids after emulsification, and has a certain degree of observation effect, but it is not as good as soybean oil as an oil additive.

[0064] It can be seen that the oil test solutions that can produce fatty acids such as soybean oil, rapeseed oil or other edible oils can produce visible color effects on the above-mentioned test samples, which proves that the test solution of the present invention can better reflect the influence of fatty acids on the permeability of PE membranes. However, the use of soybean oil as a component of the standard solution is more linearly reasonable and accurate than rapeseed oil in test data. The test data obtained from rapeseed oil are unstable in the number of color points and the color area, and cannot correctly reflect the true performance of the test product under different occasions. Therefore, it is more reasonable to use soybean oil as an additive to the test solution than rapeseed oil.

[0065] Since the material properties of PE film are basically similar to those of the above two basic materials, and combined with the above data, it can be seen that the test performance of cast film is significantly better than that of blown film products, which is also consistent with the difference in the actual performance parameters of the above materials, it means that the standard of the test method of the present invention is also in line with objective facts and can be extended to other products that are also used in the field of anti-leakage technology and its specific application is consistent.

[0066] Among them, through the content of the test results disclosed in the present invention, the following basic conclusions can be drawn: the anti-leakage performance level of the blown film product corresponding to the test results does not meet the C-level standard, and the corresponding cast film product meets the A-level standard. The measurement method is relatively easy to operate and has significant reference. Therefore, it can be explained that the test method of the present invention meets the requirements of the prior art absorbent product development, and the anti-leakage performance test requirements of other PE film samples can also be met accordingly, and it has practical value for popularization and application. At the same time, since the test method of the present invention can intuitively view the permeability of PE film products, both consumers and developers can intuitively display the defects of the PE film itself that are invisible to the naked eye, helping consumers or developers to choose suitable products more quickly and rationally.

[0067] Therefore, the present invention can reasonably and effectively classify the leakage performance levels of PE film products, especially cast film and blown film, in an intuitive, easy-to-operate and quantitative manner, and provides corresponding qualified judgment basis. PE film product developers can intuitively and accurately observe the test results that are basically consistent with the actual user experience, and quickly find the defective locations of the PE film products, so that PE film product developers can quickly and accurately identify the anti-leakage performance of the PE film through the corresponding test data, thereby finding the direction to improve the subsequent production process flow, and finding the PE film product that is most suitable for a specific application environment, thereby improving the production quality of absorbent products.

[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for detecting leakage performance of PE film material, characterized in that: include: A) Prepare the test environment, prepare a leakproof cushion, place at least one layer of plastic film on the cushion, and then place at least five layers of absorbent paper on the plastic film; B) Prepare a simulated test solution by adding 5 parts of food-grade brilliant blue and 100 parts of soybean oil standard solution to 1000 parts of normal saline and stirring evenly; C) To conduct the test, take 10 portions of the simulated test liquid, drip it onto the center of the topmost absorbent paper and let it stand for 30 seconds. Place the PE film to be tested on the absorbent paper with the use side facing up, place a piece of absorbent paper on the PE film, and then place a weight of 5 kg; D) After the test, remove the weight once at the unit time T and every time point n×T, and observe whether there is any color bleeding on the absorbent paper on the PE film each time; E) Determine the result, calculate the infiltration area and the number of infiltration surfaces, and use this as a basis to judge the leakage performance; The soybean oil standard solution comprises soybean oil, an emulsifier, 1,2-propylene glycol, and secondary pure water with a conductivity of ≤3.0 μs / cm. The soybean oil standard solution is used to simulate human urine and feces and produce fatty acids that affect the permeability of a PE membrane. The proportion of the soybean oil, the emulsifier, 1,2-propylene glycol, and the secondary pure water is 1:2:2:

100. The preparation method of the soybean oil standard solution is to pour the weighed emulsifier, soybean oil, and 1,2-propylene glycol into a beaker in sequence, stir evenly until the mixed solution has no obvious particles, pour in the secondary pure water, and stir evenly again to obtain the soybean oil standard solution.

2. The method for detecting leakage performance of PE film material according to claim 1, characterized in that: In the step E), the color bleed area and color blemishes determined by the results are based on the values ​​of the film paper stains, scratches and debris measurement charts, which include the following three grades: Class A leakage performance means that color blemishes with a color bleed area ≥3.0 square millimeters are not allowed to appear; Class B leakage performance means that the number of color bleed spots with a color bleed area of ​​1-3 square millimeters does not exceed 5; Class C leakage performance means that the number of color bleed spots with a color bleed area ≤1 square millimeter does not exceed 10.

3. The method for detecting leakage performance of PE film material according to claim 1, characterized in that: The value of T is 5 min, the value of n is 1, 2, 3, 4, 5, 6, and the value of n×T is the leakage time simulated under different usage time.

4. The method for detecting leakage performance of PE film material according to claim 2, characterized in that: The PE film includes two types: cast film and blown film, and the same judgment standard is adopted.

Citation Information

Patent Citations

  • Method for testing absorption speed, diffusion length and back-seepage quantity of paper diaper

    CN107144498A

  • Water quality ammonia nitrogen rapid detection test paper and preparation method and detection method thereof

    CN112834495A